FACTORS AFFECTING THE FREQUENCY OF CONSUMPTION OF DOMESTIC AND FOREIGN FAST FOOD BRANDS - Tomašević, Dragana; Radnović, Branislav; Gašević, Dragana (Food and Feed Research, 2020)
The rapid pace of life in recent years has led to an increase in the consumption of fast-food in all age and social groups, and in this regard to an increase in the number of newly opened fast-food restaurants. Previously conducted research work in this field has shown that various factors influence an individual’s decision (not) to consume fast-food, and the following five factors have stood out: convenience, brand reputation, quality, consistency and cost. Therefore, the aim of this research was identifying the key factors that influence the frequency of consumption of domestic and foreign fast-food brands. The sample included 146 subjects of different gender, age, qualifications, and employment status. The preliminary online research was carried out using the anonymous three-section questionnaire. Based on the data obtained through ordinal logical regression, the primary hypothesis was confirmed, as it was found that there was a statistically significant factor in the frequency of fast-food consumption, that factor being a convenience. It has been confirmed that convenience factor implies utility and time saving, the possibility of easy access to fast-food, almost 24 h working hours of fast-food restaurants and their relative proximity to the respondents. From the market point of view, a significant research result is that respondents gave preference to domestic versus foreign fast-food brands.